Farmers’ Perception Of The Implementation Of Farmer Cards Policy In Klaten Regency - Aziz Mansya Patria; Jangkung Handoyo Mulyo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2022)
The Indonesian Farmer Cards is a government policy that aims to improve the distribution pattern of subsidized fertilizers. This study aims to determine the factors that influence farmers' perceptions of implementing the farmer card policy in the Klaten Regency. Klaten Regency was selected purposively as the research site because since the inception of Farmer Card policy, Klaten Regency has been designated as a pilot location for implementing the program. The data was collected by conducting surveys and interviews by using questionnaires. Moreover, ninety-two respondents were chosen by using a simple random sampling method. Data analysis employed the Likert scale to measure farmers' perceptions of the Farmer Card Policy. Farmers’ perceptions constituted two categories based on the weighting from the Likert scale. The first category refers to farmers that have a positive perception of the application of the Farmer Card and the second category represents farmers who have negative perceptions of the program implementation. The Likert scale in this study used to determine farmers' perceptions of the application of subsidized urea fertilizer distribution policies using farmer cards in Klaten Regency. Furthermore, logistic regression determined the factors influencing farmers' perceptions. The results showed that most farmers had positive perceptions. Four variables (experience, land area, time & convenience risk, and psychological risk) positively impact the farmers' perceptions of the Farmer Card. The other variables (urea allocation) negatively affect the farmers' perception of the Farmer Card Policy.